Earnings Expectations and Capital Restructuring: The Case of Equity-for-Debt Swaps - Lys, Thomas; Sivaramakrishnan, Konduru (Journal of Accounting Research, 1988)
Equity-for-debt swaps, Earnings expectations, Information effect